Implementing sustainable ecotourism in Lafour region, Iran: Applying a clustering method based on SWOT analysis. (20th December 2021) - Hosseini, Seyyed Mehdi; Paydar, Mohammad Mahdi; Triki, Chefi
Abstract: Nowadays, one of the growing and remarkable branches of tourism is ecotourism. Ecotourism has a great impact on the development of a region from different perspectives. Hence, by improving and developing sustainable ecotourism in a region, it will be possible to develop and improve its economic, social, and environmental situation. The Lafour region is one of the potential hubs for ecotourism activities in Iran. Despite the high potential of this region for ecotourism activities, it has not yet achieved its suitable position in this domain. Hence, the main goal of this study is to develop sustainable goals for ecotourism in the region. To meet the target, first, the Strengths, Weaknesses, Opportunities, and Threats (SWOT factors) are identified through interviews with tourists, local residents, and the experts, filed observation, and considering similar works in the literature review. Then, some practical and useful strategies are determined based on SWOT analysis and consulting with the experts. The important point of the study is proposing an applicable heuristic clustering method based on SWOT analysis to classify the strategies into different clusters. To prioritize the strategies in each cluster, the commonly used Multi-Criteria Decision Making (MCDM) method called the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is applied. This paper concludes and reveals that the three strategies including ST6 "Encouraging investors and entrepreneurs to establish ecotourism centers in the region", ST5 "Establishing and improving the hygiene units and the medical clinics in the region", and ST3 "Improving and diversifying tourism services and products to attract tourists and increase their satisfaction" have the greatest impact on accomplishing sustainable development goals in the region. Highlights: The main goal of this study is to develop sustainable ecotourism in Lafour region, Iran. The SWOT are identified by the help of interviews with tourists, tourism experts, ecotourism activists, local residents and academic experts. Eight strategies are determined based on SWOT analysis and consulting with tourism experts. A heuristic clustering method based on SWOT analysis is proposed and the strategies are ranked to different clusters. The strategies in each cluster are prioritized by TOPSIS method.